Kinematics and Dynamics Analysis of Obstacle Negotiation Process for a Novel Climbing Robot - Chun Yang; Tianhong Luo (Jixie chuandong)
A wheel-foot composite wall-climbing robot which can meet different obstacle avoidance requirements is proposed, and its dynamics model is established by Kane's method. Based on the model, the adsorption force equation of the wall climbing robot in the limit motion state is deduced, and the stability margin constraints are established. The functional relationship between the minimum adsorption force satisfying the stability requirements and the limit motion state of the robot is obtained. Theoretical basis is provided for reasonable control of adsorption capacity under different obstacle avoidance working conditions.